2016
DOI: 10.1037/a0039765
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and estrogen impact social evaluations and vicarious emotions: A double-blind placebo-controlled study.

Abstract: The abilities to "read" other peoples' intentions and emotions, and to learn from their experiences, are critical to survival. Previous studies have highlighted the role of sex hormones, notably testosterone and estrogen, in these processes. Yet it is unclear how these hormones affect social cognition and emotion using acute hormonal administration. In the present double-blind placebo-controlled study, we administered an acute exogenous dose of testosterone or estrogen to healthy female and male volunteers, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 56 publications
3
36
2
Order By: Relevance
“…Prenatal T proxies (the 2D:4D, either right-hand, left-hand, or their average) did not correlate with RMET scores in both experiments or moderate the effect of T administration, echoing other recent findings (Bos et al, 2016;Carré et al, 2015;Olsson et al, 2016) (see Supplementary Material Tables S3a-S4b). These results are in line with previous reports showing no correlation between the 2D:4D and RMET scores (Hönekopp, 2012;Masuya et al, 2015;Voracek & Dressler, 2006), and in contrast to the two papers reporting an interaction between 2D:4D and the exogenous T's effect on the RMET (Carré et al, 2015;van Honk et al, 2011).…”
Section: Testing For Effect Of 2d:4dsupporting
confidence: 64%
See 3 more Smart Citations
“…Prenatal T proxies (the 2D:4D, either right-hand, left-hand, or their average) did not correlate with RMET scores in both experiments or moderate the effect of T administration, echoing other recent findings (Bos et al, 2016;Carré et al, 2015;Olsson et al, 2016) (see Supplementary Material Tables S3a-S4b). These results are in line with previous reports showing no correlation between the 2D:4D and RMET scores (Hönekopp, 2012;Masuya et al, 2015;Voracek & Dressler, 2006), and in contrast to the two papers reporting an interaction between 2D:4D and the exogenous T's effect on the RMET (Carré et al, 2015;van Honk et al, 2011).…”
Section: Testing For Effect Of 2d:4dsupporting
confidence: 64%
“…A similar experiment with roughly twice the sample size (N=33) found a much smaller 3 effect (P=0.048, one-tailed), and no moderation by 2D:4D (Olsson et al, 2016). A third experiment of 16 females found neither a main effect nor a moderation by 2D:4D (Bos et al, 2016).…”
Section: Testing Testosterone's Causal Effect On Cognitive Empathymentioning
confidence: 90%
See 2 more Smart Citations
“…T also reduces mindreading, the cognitive empathic ability whereby one infers the emotional state of the other from limited information. In women, two studies showed reduced performance on the Reading the Mind in the Eyes test after T (RMET, 9,10), and a recent functional magnetic resonance imaging (fMRI) study shows this effect can depend on reduced neural connectivity of the frontal brain regions with the anterior cingulate cortex (ACC) and premotor regions (11). In men, T has also been shown to reduce RMET performance, although with the effect being dependent on a marker for fetal T exposure (the 2D:4D ratio) and psychopathic traits (12).…”
Section: Introductionmentioning
confidence: 99%